Local Government as a Form of Democracy in Russia - Lyubashits, Valentin Y.; Lyakhov, Viktor P.; Plotnikov, Andrey A.; Voitenko, Dmitry. A.; Sokolova, Iryna A. (Journal of History Culture and Art Research, 2019)
Local government has a special place in the democratic mechanism of governing society and a state. The modernization of local self-government in post-Soviet Russia is at its early stage. Today we can only talk about some positive trends in this process. First of all, it should be noted that local self-government has both a special subject, which is the population, citizens and a special object of management: issues of local importance. Besides, one of the basic concepts that characterize the essence of local self-government as a form of organization and exercise of power is independence. Like any other form of social self-government, local government is a powerful means of activating a political system, democratic institutions, individual citizens, and of combating bureaucracy and formalism in the work of state governing bodies. The definition of the socio-political nature of the local self-government draws attention to it, first of all, by its pronounced democratic essence. The formation of local government is a long process, and its implementation should be carried out on a systematic (planned) basis in the form of a state program. However, self-government is not only the basis of democracy. Self-government and self-governing groups are the highest forms of integration of people, corresponding to the very nature of a man. This paper is dedicated to the main milestones of evolution of the local government in Russia.